Prevention of myelosuppression by combined treatment with enterosorbent and granulocyte colony-stimulating factor - Shevchuk, O.O.; Posokhova, K.A.; Todor, I.N.; Lukianova, N.Yu.; Nikolaev, V.G.; Chekhun, V.F. (Experimental Oncology, 2015)
Hematotoxicity and its complication are the prominent limiting factors for rational treatment of malignancies. Granulocyte colony-stimulating factor (G-CSF) is used to increase granulocyte production. It has been shown previously that enterosorption causes prominent myeloprotective activity also. Still, no trial was performed to combine both of them. Aim: To study the influence of combination of enterosorption and pharmaceutical analogue of naturally occurring G-CSF (filgrastim) on bone marrow protection and the growth of grafted tumor in a case of injection of melphalan (Mel). Materials and Methods: Mel injections were used for promotion of bone marrow suppression in rats. Carbon granulated enterosorbent C2 (IEPOR) was used for providing of enteral sorption detoxifying therapy. Filgrastim was used to increase white blood cells (WBC) count. Results: The simultaneous usage of enterosorption and filgrastim had maximum effectiveness for restoring of all types of blood cells. WBC count was higher by 138.3% compared with the Mel group. The increase of platelets count by 98.5% was also observed. In the group (Mel + C2 + filgrastim) the absolute neutrophils count was twofold higher, in comparison with rats of Mel group. Conclusion: Simultaneous administration of G-CSF-analogue and carbonic enterosorbent C2 is a perspective approach for bone marrow protection, when the cytostatic drug melphalan is used. Such combination demonstrates prominent positive impact on restoring of all types of blood cells and had no influence on the antitumor efficacy. Key Words: myelotoxicity, melphalan, enterosorption, granulocyte colony-stimulating factor.